Act forward, look backward - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Learning about capacity development through evaluation:Perspectives and observations from a collaborative network of national and international organizations and donor agencies By D Horton, CTA co-publication ISNAR, meeting report No 13. 2001. 52 pp.